Influence of SO2 on heterogeneous reaction between NO and char - Abd. Halim Shamsuddin ,; B.M. Gibbs, (1989)
Reactions between NO and char were investigated in a fluidised bed reactor in the presence of SO2. The reaction between NO and char is enhanced in the presence of SO2. NO conversion was found to increase by about 50 to 100% when 1250 p.p.m. SO2 were present in the fluidising gas mixture. The products of the reactions are CO/CO2 and N2 with the CO/CO2 ratio decreasing as the SO2 concentration is increased. The SO2 concentration was found to be unaffected by the NO/char reaction